1975
DOI: 10.1007/bf00421304
|View full text |Cite
|
Sign up to set email alerts
|

Acute tolerance to ethanol in the rat

Abstract: Male Wistar rats were examined on the moving belt test at approximately 10, 30 and 60 min after administration of ethanol in doses ranging from 1.0-2.8 g/kg. Immediately after the test, each animal was sacrificed and ethanol concentrations were measured. The regression line of impairment as a function of brain alcohol concentration showed a progressive shift toward higher brain levels with increasing time after alcohol administration. The results confirm the existence of acute tolerance to ethanol, as defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(52 citation statements)
references
References 11 publications
3
48
0
1
Order By: Relevance
“…Impairment, measured as time off of the belt was regressed against brain ethanol concentrations immediately after the test. The regression line of impairment as a function of brain ethanol concentration showed a progressive rightward shift (toward higher effective brain concentrations) with increasing time after alcohol administration (LeBlanc et al, 1975). Others have extended these findings by demonstrating that practice during intoxication enhances the development of acute tolerance in this procedure (Lê and Kalant, 1992).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Impairment, measured as time off of the belt was regressed against brain ethanol concentrations immediately after the test. The regression line of impairment as a function of brain ethanol concentration showed a progressive rightward shift (toward higher effective brain concentrations) with increasing time after alcohol administration (LeBlanc et al, 1975). Others have extended these findings by demonstrating that practice during intoxication enhances the development of acute tolerance in this procedure (Lê and Kalant, 1992).…”
Section: Introductionmentioning
confidence: 82%
“…LeBlanc et al, (1975) trained rats to stay on a moving belt. Subjects that stepped off of the belt received a mild electric shock.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experiments with animals and humans during the last century have compared the effect of alcohol on motor performance during rising and declining limbs of the blood alcohol curve. These experiments have shown that the impairing effect of a given blood alcohol concentration (BAC) is greater on the rising than on the declining limb of the curve (eg LeBlanc et al, 1975;Mellanby, 1919;Vogel-Sprott and Fillmore, 1993). This reduction in impairment observed during declining BACs suggests some process of adaptation or habituation may occur during physiological exposure to a dose of alcohol (Kalant et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…However, even a single use of the drug gives rise to "opponent processes" (Koob, 2009) that are opposite in direction to the effect of the drug and thus produce a progressive decrease in drug effect, recognized as acute tolerance. After elimination of the drug the opponent processes are manifested as an acute withdrawal effect (LeBlanc, Kalant, & Gibbins, 1975;McQuarrie & Fingl, 1958). Repeated heavy use of the drug leads to longer-…”
Section: Changing Concepts Of Addictionmentioning
confidence: 99%